Irisin Pretreatment Protects Kidneys against Acute Kidney Injury Induced by Ischemia/Reperfusion via Upregulating the Expression of Uncoupling Protein 2. (31st August 2020) - Zhang, Rui; Ji, Jing; Zhou, Xiaoshuang; Li, Rongshan
Abstract : As a common disorder, acute kidney injury (AKI) is characterized by high mortality and morbidity, and current therapeutic options for AKI remain limited. Irisin, a muscle factor, plays an important role in metabolic disorders. However, the role of irisin in AKI is still unclear. To assess the effect of irisin on the course of AKI, we used an ischemia/reperfusion (I/R) C57BL/6 mouse model. Supplementation with irisin attenuated kidney injury induced by I/R, as shown by decreases in the levels of serum creatinine and blood urea nitrogen. Animal model studies also showed that irisin pretreatment upregulates the expression of uncoupling protein 2 (UCP2) and protects against the renal cell apoptosis and oxidative stress caused by I/R. In vitro, hypoxia/recovery (H/R) treatment was applied to induce tubular cell apoptosis. Irisin pretreatment ameliorated the cell apoptosis induced by H/R, while transfection of UCP2 siRNA significantly reduced the protective effect of irisin in cells after H/R. In addition, AMPK signaling may be involved in irisin-mediated upregulation of UCP2 in a renal proximal tubular epithelial cell (PTEC) model. Thus, the renoprotective effect of irisin on AKI may be mediated through increasing the expression of UCP2 in kidneys after I/R.